2021
DOI: 10.1088/1755-1315/648/1/012101
|View full text |Cite
|
Sign up to set email alerts
|

Rainwater harvesting technology to increase cropping index under perennial crops

Abstract: Spatial and temporal water availability uncertainties are the major constraints to dryland crops productivity. Comprehensive hydrologic survey to determine water harvesting location as supplementary irrigation source is the key to increase dryland cropping index. This research was conducted in Lampung during April to December 2019. The aims of this research were to develop water management designs and irrigation techniques for upland rice and maize cultivation under perennial crops. The applied irrigation tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
3
0
2
Order By: Relevance
“…In our review of several other studies, we found some interesting results. Heryani et al [21,22] conducted a study to develop water management strategies and irrigation systems for highland agriculture purposes. The study revealed changes in crop yield and determined the need to enhance irrigation systems through water-harvesting techniques in the highlands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our review of several other studies, we found some interesting results. Heryani et al [21,22] conducted a study to develop water management strategies and irrigation systems for highland agriculture purposes. The study revealed changes in crop yield and determined the need to enhance irrigation systems through water-harvesting techniques in the highlands.…”
Section: Discussionmentioning
confidence: 99%
“…Wide-ranging hydrological studies have been conducted to examine the natural water storage, and evaluating sites for irrigation purposes is the key to strengthening dryland farming [22]. Dryland agriculture practices are threatened by uncertainties in spatialtemporal water accessibility and crop yield.…”
Section: Introductionmentioning
confidence: 99%
“…Embung berfungsi untuk menampung air baik dari air hujan, air sungai, air tanah yang bermanfaat untuk mengurangi dampak banjir dari besarnya volume air pada musim hujan serta menyimpan cadangan air sebagai sumber untuk memenuhi kebutuhan air irigasi di musim kemarau pada lahan pertanian (Heryani et al, 2021). Dalam merencanakan dimensi bangunan embung, diperlukan analisis hidrologi serta neraca air untuk menentukan tinggi tubuh embung dan kapasitasnya (Budiyanto & Suharyanto, 2022;Dewi & Wahidin, 2020) Kebutuhan air dalam irigasi pertanian merupakan komponen utama yang dapat mempengaruhi pertumbuhan dan produksi tanaman, sehingga diperlukan kondisi penilaian suatu sistem agar terpenuhi keseimbangan melalui pendekatan konsep neraca air.…”
Section: Pendahuluanunclassified
“…Namun, jika air disalurkan tidak sesuai kebutuhan dapat menyebabkan kekeringan atau banjir pada lahan (Heryani et al, 2017)…”
Section: Table 1 Produksi Padi (Ton) Jawa Baratunclassified